Analyzing the Impact of Systems, Human Capital, and Anti-Bribery Practices on Business Satisfaction: The Case of Halal Certification in Indonesia - Fauziah Fauziah; Ibnu Hasan Muchtar; Miguel Angel Esquivias; Siti Hafsah Zulkarnain; Rosa Melia Maharani; Novita Eka Wulandari (Journal of Islamic Monetary Economics and Finance, 2026)
Maintaining good service quality in halal certification procedures has become crucial as the demand for halal products grows globally. Focusing on Indonesia, this study investigates the relationship between firm satisfaction with halal certification services and support systems, human capital, and anti-bribery practices. The study uses Structural Equation Modelling (SEM) and the SERVQUAL framework to analyze survey data from 2,367 businesses with halal certifications in 32 Indonesian provinces.  The aim is to reveal the determinants of satisfaction and the impact of institutional performance on service delivery. The findings demonstrate that employees with responsiveness, empathy, assurance, and good communication significantly improve not only the perceived quality of services but also the efficacy of anti-bribery initiatives.  Meanwhile, support systems that enhance employee performance and customer satisfaction include sufficient equipment, transparent quality control, and complaint procedures. These findings highlight that integrity and professionalism are just as important as technical systems to make certification successful. This study provides insights for certifying organizations and legislators in formulating strategies to boost the competitiveness of Indonesia's halal market, increase efficiency, and build confidence. Strengthening institutional capacity and reducing bureaucratic barriers can help ensure a more reliable and business-friendly certification ecosystem. Acknowledgment This work was supported by Airlangga University under the Research Scheme “Penelitian Unggulan Halal” (Grant Number: 63/ST/UN3. HALAL/PT.March 01, 2024).